Pengaruh Promosi Jabatan dan Rekan Kerja Terhadap Kepuasan Kerja Pegawai PDAM Tirtanadi Cabang Sei Agul Medan - Juniarti, Juniarti; Nasution, Sarifa Ulfa (Pusat Riset dan Inovasi Nasional, 2022)
Experienced against a variety of a company engaged in the field of services of clean water. Where PDAM TIrtanadi Cabang Sei Agul Medan has some problems, these problems is the number of employees who have not been promoted due to the background educational background that is not appropriate, less the intertwining relations good work among employees and the number of errors conducted employee during the work. The method used ini this research is quantitavive apporoach with a type of reseach based on the philosophy of positivism. The results of the research on the hypotheses showed that job promotion and co-workers simultaneously affect job satisfaction. The results of this study showed that job promotion partially and significantly affect job satisfaction and co-workers partially and significantly affect job satisfaction. Simultaneously and partially the job promotion and co-workers positively and significantly affect the job satisfaction of employees of PDAM Tirtanadi Cabang Sei Agul Medan and the value of the coefficient of determination of 62,3% and the remaining 37,7 described by independent variables that were not studied.